Ultra-overt therapy: a novel medical approach centered on patient consciousness - Shirbache, Kamran; Liaghat, Amirreza; Saeifar, Sanam; Nezameslami, Ahmadreza; Shirbacheh, Ali; Nasri, Hamid; Namazi, Hamidreza (Frontiers in Integrative Neuroscience, 2024)
Within the realms of human and artificial intelligence, the concepts of consciousness and comprehension are fundamental distinctions. In the clinical sphere, patient awareness regarding medication and its physiological processes plays a crucial role in determining drug efficacy and outcomes. This article introduces a novel perspective on prescription practices termed “Ultra-Overt Therapy” (UOT). A review of current supporting evidence was conducted through a non-systematic search in PubMed and Google Scholar, focusing on concepts such as the “mind–body relationship,” “placebo response,” “neuroscience,” and “complementary medicine.” Our findings, rooted in the mechanisms of the “placebo effect,” the intricacies of “intersubjective therapy,” the potency of “interoceptive awareness,” and other domains of medical science, suggest that UOT holds theoretical promise. Future research endeavors focusing on these areas may elucidate the global impact of this method on medical treatment and patient care.